2012
DOI: 10.1186/1746-1596-7-79
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T-cell Lymphoma with Cyclin D1 overexpression: a case report

Abstract: Peripheral T-cell lymphomas not otherwise specified are generally considered aggressive non-Hodgkin lymphomas, because of poor natural outcome and response to therapy. They show a complex karyotype without any specific genetic hallmark. We report a case of peripheral T-cell lymphoma not otherwise specified with heterogeneous nuclear Cyclin D1 immunohistochemical overexpression, due to gene copy gain, a phenomenon similar to that observed in Mantle Cell Lymphoma characterized by t(11;14)(q13;q32). In this case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
1
7
0
1
Order By: Relevance
“…It can activate CDK4 or CDK6 to phosphosphorylate a series of key substrates, such as protein Rb, in that case, the transcription factors will be released to promote synthesis of DNA and accelerate the cells proliferation [ 17 ]. Thus it is an essential sensor and activator of cell cycle initiation and progression; Cyclin D1 amplification and gain copies with consequent protein over-expression have been frequently described in multiple myeloma, T cutaneous lymphomas and in solid cancer [ 18 ], such as oral squamous cell carcinoma, lung cancer, melanoma, breast cancer [ 19 , 20 ]. A recent study has shown that strong nuclear EGFR expression in colorectal carcinomas is associated with cyclin-D1 but not with gene EGFR amplification [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can activate CDK4 or CDK6 to phosphosphorylate a series of key substrates, such as protein Rb, in that case, the transcription factors will be released to promote synthesis of DNA and accelerate the cells proliferation [ 17 ]. Thus it is an essential sensor and activator of cell cycle initiation and progression; Cyclin D1 amplification and gain copies with consequent protein over-expression have been frequently described in multiple myeloma, T cutaneous lymphomas and in solid cancer [ 18 ], such as oral squamous cell carcinoma, lung cancer, melanoma, breast cancer [ 19 , 20 ]. A recent study has shown that strong nuclear EGFR expression in colorectal carcinomas is associated with cyclin-D1 but not with gene EGFR amplification [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The final diagnosis in this case also underlined this point. In addition, as same as other T-lymphomas occurred in uncommon sites [12-16], the gastric EATL also exhibits the genetic disorder which will be helpful to distinguish from reactive process.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, morphologically, middle to large-sized neoplastic cells with atypia and mitosis can be detected in T cell lymphoma and ANKL. However, as previously mentioned, the characteristic T-cell makers, rearranged TCR gene, and have no relation to EBV infection are distinguishing features [14,15]. …”
Section: Discussionmentioning
confidence: 99%